Empowering Student-Centered Learning in English Education (A Closer Look at Kurikulum Merdeka) - Putu Sri Darmayanti (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2023)
This study aims to Empowering Student-Centered Learning in English Education (A Closer Look at Kurikulum Merdeka). This research is a literature review. Data collection techniques are documentation from journal sources and relevant literature such as Google Scholar. Data analysis with critical literature. research results Empowering student-centered learning in English education, especially in the context of the Independent Curriculum, is an approach that focuses on developing students' abilities holistically. This approach prioritizes students' active role in the learning process, enabling them to take a central role in exploring their English knowledge and skills. In the context of the Independent Curriculum, students have more freedom to determine their own learning path, while the teacher acts as a facilitator. As such, these conclusions reflect that this approach has the potential to increase student motivation and learning outcomes in English, while supporting a vision of learning that is more independent and centered on individual needs in the education system.